2014
DOI: 10.1002/2013je004476
|View full text |Cite
|
Sign up to set email alerts
|

Global assessment of pure crystalline plagioclase across the Moon and implications for the evolution of the primary crust

Abstract: Recent advancements in visible to near infrared orbital measurements of the lunar surface have allowed the character and extent of the primary anorthositic crust to be studied at unprecedented spatial and spectral resolutions. Here we assess the lunar primary anorthositic crust in global context using a spectral parameter tool for Moon Mineralogy Mapper data to identify and map Fe-bearing crystalline plagioclase based on its diagnostic 1.25 μm absorption band. This allows plagioclase-dominated rocks, specifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
87
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(104 citation statements)
references
References 84 publications
13
87
0
Order By: Relevance
“…This scenario also implies that peak rings should come from relatively shallow crustal levels, controlled by the geometry of the excavation and melting cavities. These predictions on stratigraphic uplift are consistent with the abundance of pure crystalline anorthosite in many of the peak rings of basins on the Moon (Hawke et al, 2003;Yamamoto et al, 2012;Cheek et al, 2013;Donaldson Hanna et al, 2014;Baker and Head, 2015). However, the hypothesized regions of stratigraphic uplift are distinct from the estimated stratigraphic uplift of central peaks in complex craters, which are commonly inferred to be constrained by the maximum depth of melting (Cintala and Grieve, 1998a,b;Tompkins and Pieters, 1999).…”
Section: Modification Stagesupporting
confidence: 63%
See 2 more Smart Citations
“…This scenario also implies that peak rings should come from relatively shallow crustal levels, controlled by the geometry of the excavation and melting cavities. These predictions on stratigraphic uplift are consistent with the abundance of pure crystalline anorthosite in many of the peak rings of basins on the Moon (Hawke et al, 2003;Yamamoto et al, 2012;Cheek et al, 2013;Donaldson Hanna et al, 2014;Baker and Head, 2015). However, the hypothesized regions of stratigraphic uplift are distinct from the estimated stratigraphic uplift of central peaks in complex craters, which are commonly inferred to be constrained by the maximum depth of melting (Cintala and Grieve, 1998a,b;Tompkins and Pieters, 1999).…”
Section: Modification Stagesupporting
confidence: 63%
“…Peak rings on the Moon typically show outcrops of predominantly pure crystalline anorthosite and more noritic lithologies (Hawke et al, 2003;Whitten et al, 2011;Yamamoto et al, 2012;Cheek et al, 2013;Donaldson Hanna et al, 2014;Baker and Head, 2015). An exception is in regions of thinned crust such as the interior of the South Pole-Aitken basin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a telescopic study, Spudis et al (1984) suggested the presence of anorthosite, not by the presence of a 1.25-μm band but by the lack of other mafic absorption bands. In the past decade, high spectral and spatial resolution VNIR reflectance data sets from the SELENE Spectral Profiler (SP) and Multiband Imager (MI) and the Chandrayaan-1 Moon Mineralogy Mapper (M 3 ) have identified iron-bearing crystalline plagioclase with its characteristic 1.25-μm absorption band in diverse regions on the Moon (Cheek et al, 2013;Donaldson Hanna et al, 2014;Matsunaga et al, 2008;Ohtake et al, 2009;Pieters et al, 2009). Clementine ultraviolet-visible (UVVIS) imaging data sets examined the central peaks of over 100 impact craters across the Moon and demonstrated that the lunar crust is extremely anorthositic (Tompkins & Pieters, 1999).…”
Section: Plagioclase On the Moon Mars And Asteroids 211 Plagioclmentioning
confidence: 99%
“…Plagioclase consists a series of compositions from albite (NaAlSi 3 O 8 ) to anorthite (CaAl 2 Si 2 O 8 ) that indicate changing conditions during fractional crystallization. On the Moon, VNIR spectroscopy has been used to identify pure plagioclase using this feature only in areas that lack mafic phases (Cheek et al, 2013;Donaldson Hanna et al, 2014). This band, however, is easily masked by <15 vol.% of mafic phases, such as pyroxene or olivine (Crown & Pieters, 1987;Nash & Conel, 1974).…”
Section: Introductionmentioning
confidence: 99%